ON CLS- MODULES - Sahib, Lmyaa; AL-Bahraany, Bahar (Iraqi Journal of Science, 2023)
Let R be a commutative ring with identity and let M be a unital left R-module.A.Tercan introduced the following concept.An R-module M is called a CLSmoduleif every y-closed submodule is a direct summand .The main purpose of thiswork is to develop the properties of y-closed submodules.